2-Quasi crossed modules of commutative algebras - Kadir, Emir (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 512.6We define 2-quasi crossed modules of commutative algebras obtained by relaxing some 2-crossed module conditions. Moreover, we prove that there exists a functorial relationship between these two structures which enables us to construct the coproduct object in the category of 2-crossed modules of commutative algebras.